English Teaching Learning Process For Slow Learner In Inclusive Class At Smp Al FirdausIn 2016/2017 Academic Year - Muliasari, Dewi; , Dr. Anam Sutopo, M.Hum; , Mauly Halwat Hikmat, Ph.D (2017)
Inclusive education is a regular education which covers children with special needs inside. Through inclusive education, children with special needs are able to study together with normal students. So that there is no discrimination toward students with special needs. One kind of student with special needs with is slow learners. Slow learner is a students who has low level of mastering the material, slow learner cannot be classified as mental retardation. The objectives of this researh are intended to get clear description of the Englih teaching learning process of inclusive class at SMP Al Firdaus. It covers; (1) the preparation of the teacher before teaching learning process, (2) the phase of English teaching learning process, (3) the problems faced by slow learner student; and (4) the solution toward the problem. The type of this research was a qualitaive research. The subjects of this research were the English teacher and also shadow teacher. While the object of this research was the English teaching learning process for slow learner in inclusive class at class A of eight grade in SMP Al Firdaus. The data were collected using several techniques including observation, interview, and document analysis. The triangulstion method was used to examine the data from interview with the result of observation and source triangulation to examine the information with the document.The results of this study showed that in the preparation of the teacher, subject I as an English teacher prepared media and learning resources, lesson plan, and also syllabus. While teacher R as shadow teacher did not prepare syllabus and lesson plan but she only prepared special media, learning resources, and individualized Educational Program for slow learner. The phases of the English teaching learning processes were done through three stages; the first, pra-instructional stage, instructional stage, and evaluation. In English teaching learning process there were some problems faced by slow learner and teacher I alongsides teacher R have some ways to solve the problems faced by slow learner. Both teacher I and also teacher R said that the main problem faced by slow learner is that slow learner is lack of vocabulary and he also has difficulty in memorizing new vocabulary. The solution is teacher I as English teacher always asks him to translate and teacher R as his shadow always gives him list of vocabulary related to the material.